2018
DOI: 10.1002/anie.201812426
|View full text |Cite
|
Sign up to set email alerts
|

Assembling a Hybrid Pd Catalyst from a Chiral Anionic CoIII Complex and Ligand for Asymmetric C(sp3)–H Functionalization

Abstract: An unusual hybrid palladium catalyst containing an anionic chiral CoIII complex and a chiral phosphoramidite ligand shows a high capacity for catalyzing asymmetric thioamide‐directed C(sp3)−H arylation and delivers excellent yield and enantioselectivity (up to 99 % yield, 99 % ee). Significant synergy between the chiral ligand and the anion in terms of stereochemical control was observed. Mechanistic investigations have revealed both the nature of the C−H activation and the origin of the enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 79 publications
2
30
0
1
Order By: Relevance
“…It should be noted that recently Gong, Wu, and Zhang have reported an anionic chiral Co III complex that is critical in an asymmetric C(sp 3 )-H functionalization. 42 This complex resembles the above presented intermediate C 0 .…”
Section: Anionic Reaction Pathwaysupporting
confidence: 66%
“…It should be noted that recently Gong, Wu, and Zhang have reported an anionic chiral Co III complex that is critical in an asymmetric C(sp 3 )-H functionalization. 42 This complex resembles the above presented intermediate C 0 .…”
Section: Anionic Reaction Pathwaysupporting
confidence: 66%
“…As shown in Scheme a, Yu and co‐workers reported an enantioselective amine α‐C(sp 3 )−H arylation of thioamides afforded by combining a chiral phosphoric acid (CPA) with a palladium catalyst . We found that a hybrid palladium catalyst containing a chiral Co III ‐complex anion and a chiral phosphoramidite ligand is highly efficient for a similar reaction, delivering up to 99 % yields and 99 % ee . Using a chiral phosphoramidite ligand, Glorius and co‐workers established an asymmetric Rh I ‐catalyzed amine α‐arylation of 1,2,3,4‐tetrahydroquinolines bearing a tert ‐butyl thioamide directing group .…”
Section: Methodsmentioning
confidence: 99%
“…Gong et al [44] described an improved protocol to achieve enantioselective arylation of α-CÀ H bonds in cyclic amines 34 using a chiral anionic Co(III)- complex with Pd-catalyst and a chiral phosphoramidite ligand (see Scheme 7). Aryl boronic acids 35 was used as the coupling partner for the arylation.…”
Section: α-Cà H Activation and Functionalization Of Aminesmentioning
confidence: 99%
“…CÀ H activation and enantioselective arylation using thioamide DG. intermediate 42 and hence C(sp 2 )À H bond activation (43) was involved in the process followed by carboncarbon bond formation (44).…”
Section: α-Cà H Activation and Functionalization Of Aminesmentioning
confidence: 99%